Closing the Gap between People and Programs: Lessons from Implementation of Social Accountability for Family Planning and Reproductive Health in Uganda - Boydell, Vicky; Neema, Stella; Wright, Kelsey; Hardee, Karen (African journal of reproductive health, 2018)
Globally, women‘s access to modern contraception can be attributed to poor service conditions and care. Growing evidence from across the health sector has found that social accountability approaches have the potential to improve the quality of care and therefore the utilization of health services, little of this evidence relates to family planning and reproductive health programs. This paper therefore assessed the results of retrospective implementation research into a five-year social accountability project in Uganda that focused on family planning and reproductive health. A mix of methods was used examine the project‘s implementation in three districts in Uganda between 2009 to 2013, including political economy analysis, document review, and in-depth interviews. Interviews were coded using ATLAS.ti software and analyzed with a thematic framework, organized by stakeholder groups and across districts. The research found that while the project broadly delivered as intended in local accounts, a wider range of activities and outcomes also occurred. Community participants in the three districts were much more likely to remember more personal changes, such as increased confidence when interacting with health care providers, in their health seeking behavior or in their ability to represent themselves. The research revealed a web of accountability relationships at play. These ranged from formal opportunities for community participation in institutional processes, to the more personal direct relationship between the service users and the health care provider compared to the less direct relationship between the community and local officials. In addition, ways in which elements of social accountability can be combined with features of FP program were seen, such as including outreach activities with civic and rights education. This appears to extend the reach and credibility of these services among community members while also counteracting barriers to women‘s and young people‘s participation.
Keywords: Social accountability; Family planning; Reproductive health; Implementation science